Analyzing the present condition of market to become a market leader in dairy sector: BRAC dairy & food project (Aarong dairy) - Israt, Khadija (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016